Gene encoding the CTP synthetase as an appropriate molecular tool for identification and phylogenetic study of the family Bifidobacteriaceae - Killer, Jiří; Mekadim, Chahrazed; Pechar, Radko; Bunešová, Věra; Mrázek, Jakub; Vlková, Eva (MicrobiologyOpen, 2018)
An alternative molecular marker with respect to the 16S rRNA gene demonstrating better identification and phylogenetic parameters has not been designed for the whole Bifidobacteriaceae family, which includes the genus Bifidobacterium and scardovial genera. Therefore, the aim of the study was to find such a gene in available genomic sequences, suggest appropriate means and conditions for asmplification and sequencing of the desired region of the selected gene in various strains of the bacterial family and verify the importance in classification and phylogeny. Specific primers flanking the variable region (~800 pb) within the pyrG gene encoding the CTP synthetase were designed by means of gene sequences retrieved from the genomes of strains belonging to the family Bifidobacteriaceae. The functionality and specificity of the primers were subsequently tested on the wild (7) and type strains of bifidobacteria (36) and scardovia (7). Comparative and phylogenetic studies based on obtained sequences revealed actual significance in classification and phylogeny of the Bifidobacteriaceae family. Gene statistics (percentages of mean sequence similarities and identical sites, mean number of nucleotide differences, P- and K-distances) and phylogenetic analyses (congruence between tree topologies, percentages of bootstrap values >50 and 70%) indicate that the pyrG gene represents an alternative identification and phylogenetic marker exhibiting higher discriminatory power among strains, (sub)species, and genera than the 16S rRNA gene. Sequences of the particular gene fragment, simply achieved through specific primers, enable more precisely to classify and evaluate phylogeny of the family Bifidobacteriaceae including, with some exceptions, health-promoting probiotic bacteria.
Keywords: bakteriální proteiny; techniky typizace bakterií; Actinobacteria; Bacterial Proteins; DNA Primers; Carbon-Nitrogen Ligases; DNA, Bacterial; Phylogeny; RNA ribozomální 16S; RNA, Ribosomal, 16S; ligasy tvořící vazby C-N; fylogeneze; DNA primery; DNA bakterií; Bacterial Typing Techniques